Gender, Race, and Minority Stress Among Sexual Minority Women: An Intersectional Approach - Everett, Bethany G. (Arch Sex Behav, 2019)
Previous research examining the relationship between gender-role presentation and minority stress has largely focused on the negative effects of gender nonconformity. Some research suggests, however, that gender-role nonconformity may be protective against minority stress via participation in sexual minority in-group norms, which may include rejecting traditional gender-role norms and gender presentation. Historically, the meaning and value of masculinity and femininity within sexual minority communities has varied by race/ethnicity. As such, race/ethnicity may moderate the links between gender and minority stressors. This study used a diverse sample of sexual minority women (SMW) (N = 612) and separate indicators of masculinity and femininity to examine the effects of gender role on distal (victimization and discrimination) and proximal (internalized homophobia and stigma consciousness) measures of minority stress. We used multivariate generalized linear models to determine whether the effects of masculinity and femininity on the minority stress outcomes were moderated by race/ethnicity. We found that in many cases the relationships between masculinity and femininity and minority stress varied across racial/ethnic groups, and in fact, worked in opposite directions for White SMW compared to Black and Latina SMW. For example, our results showed that masculinity was associated with lower levels of victimization, discrimination, and stigma consciousness among Black and Latina SMW, but higher levels among White SMW. Results from this study suggest that these differences have important implications for exposure to minority stress.